Summer Cosmos â A Host of Cucumber mosaic virus (Journal of Agriculture & Rural Development, 2008)
In order to identify the cause of virus disease-like symptoms developed naturally in Summer cosmos (Cosmos sulphureus) plants at Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur campus, a study was conducted during March 2004 to August 2005. The natural symptoms in Summer cosmos were consisted of mosaic, yellowing, shoe-string and leaf curling along with severe stunting of the infected plants. The ailments were found to be sap transmissible. Gomphrena globosa and Chenopodium amaranticolor were found to be good local lesion hosts producing chlorotic local lesion in the inoculated plants. The virus isolates obtained from the infected G. globosa plant had wide host range including Amaranthaceae, Chenopodiaceae, Compositae, Cucurbitaceae, Ligominosae and Solanaceae. The dilution end point, thermal inactivation point and longevity in vitro were determined as 10-6, 65Â°C and 10 days, respectively. The host range test, dilution end point, thermal inactivation point and longevity in vitro suggested that the virus was identical to Cucumber mosaic virus (CMV). Double Antibody Sandwich Enzyme-Linked Immuno-Sorbent Assay (DAS-ELISA) detected the virus as CMV. The results of the study revealed that the virus disease-like symptoms naturally manifested in summer cosmos plants was identified as CMV. Key words: Summer cosmos, CMV, virus identification. DOI = 10.3329/jard.v5i1.1463 J Agric Rural Dev 5(1&2), 84-93, June 2007